SYNTHESIS AND CHARACTERIZATION OF MAGNETITE FE3O4 NANOPARTICLES FROM NATURAL IRON SAND in GELAR RIVER - Mardana, Ida Bagus Putu; Nur Lutfiyah, Yoni; Yasa, Putu; Agung Widiantara, Gusti Kade (Indonesian Physical Review, 2024)
Fe3O4 nanoparticles made from the natural iron sands of the Gelar River have been successfully synthesized using the coprecipitation method. Test the content of Fe elements in pure iron sand and characterize them using XRF after separation. Fe3O4 nanoparticle characterization uses XRD to determine the sample's lattice parameters and crystal size. The nanoparticles' morphology, structure, particle shape, and elemental content were characterized using SEM-E DX. Magnetic properties and magnetic saturation values are characterized using VSM. XRF yield on iron sand before separation contains Fe 59.46%. After separation, the Fe content rose to 84.72%. The synthesis results obtained brownish-black Fe3O4 nanoparticle powder that permanent magnets can attract. Based on the XRD results, the crystal structure formed is cubic inverse spinel with crystal lattice Â Ã… with a particle size of 14.8 nm. The SEM-EDX results show the morphology of spherical nanoparticles with multiple agglomerations. Particle size is 40 nm. The EDX spectrum confirmed the formation of Fe3O4 nanoparticles in the presence of Fe (51.79%) and O (25.68%). The VSM results show that Fe3O4 samples have ferromagnetic properties with saturation magnetization (MS) = 27.36 emu/g, remanent magnetization (Mr) = -0.01 emu/g, and coercivity field (Hc) = 0.01 T.